2020
DOI: 10.7759/cureus.8759
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Stereotactic Body Radiation Therapy for Seven Ipsilateral Lung lesions

Abstract: Bernard et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In May 2020, Bernard et al reported the case of a patient with five metastatic lung lesions that were treated synchronously with SBRT, followed by two additional lesions also treated synchronously with SBRT, for a total of seven lesions in the same lung, separated by less than 5 cm. After a 14-month follow-up, the authors found no progression and no significant late side effects [ 71 ].…”
Section: Eligible Patientsmentioning
confidence: 99%
“…In May 2020, Bernard et al reported the case of a patient with five metastatic lung lesions that were treated synchronously with SBRT, followed by two additional lesions also treated synchronously with SBRT, for a total of seven lesions in the same lung, separated by less than 5 cm. After a 14-month follow-up, the authors found no progression and no significant late side effects [ 71 ].…”
Section: Eligible Patientsmentioning
confidence: 99%
“…We know that studies have been conducted on patients with multiple lung metastases. Bernand et al conducted a study on a patient with seven metastases in one lung and recommended the use of SBRT, especially in metastatic patients with a high possibility of survival (13). Kelly (15).…”
Section: Introductionmentioning
confidence: 99%